ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE ON PAYOUT RATIO DEVIDENDS IN COMPANIES REGISTERED IN JAKARTA ISLAMIC INDEX (JII) 2012-2016: ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP DEVIDEN PAYOUT RATIO PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2012-2016 - Ermawati, Eka (International Journal of Management and Business (IJMB), 2023)
One of the company's financial policies is dividend payment to investors who have invested their funds in the company in the form of shares. This policy is known as the Dividend Payout Ratio. The population in this study were all companies listed on the Jakarta Islamic Index (JII) in 2012-2016. While the sample in this study is to use purposive sampling technique. Data analysis methods used are descriptive statistical tests, normality, and hypotheses. The results of this study are of the 6 variables studied (operating cash flow, turn on assets, Debt to Equity Ratio, Return on Equity and Asset Growth), the most dominant in the mean value is DER. Partially only the Asset Gowth variable has a negative value on the dividend payout ratio, the other variables are positive. Simultaneously, the 6 variables studied (Operating Cash Flow, Turn On Asset, Debt to Equity Ratio, Return On Equity and Asset Growth) have a positive and significant effect on the Dividend Payout Ratio